Two systems of desinclusion of retained teeth: system means crossbow and mouse trap system - Soldevilla Galarza, Luciano (2006)
The presence of retained teeth is very common in children, excluding third molars, they are the most frequently. Most of these teeth are exposed surgically following its orthodontic direction within the dental arches. In orthodontic treatrnent we have the system "Ballista Spring" and the "Mouse Trap" that will allow us the solve limitations of another systems.